A Cross-Sectional Study of Faith-Based Global Health Organizations to Assess the Feasibility of a Christian Research Collaborative - Jason Paltzer; Keyanna Taylor (Health for All Nations, 2021)
Background: Religiosity and spirituality are recognized determinants of health, yet many faith-based organizations do not conduct or publicly disseminate research or evaluation data to inform practice. The purpose of this study was to assess the feasibility of establishing a collaborative to support small to medium-sized, Christian, global health organizations in producing stronger evidence regarding the practice and application of integral mission health models. Methods: A cross-sectional study was done using a digital, mixed-method (open- and closed-ended questions) survey. The survey was distributed through a convenience sample of Christian global health networks and member organizations representing over 1,000 primarily small to medium sized organizations. Information was collected regarding organizational research and evaluation publication/presentation experience, collaborative interests, evaluation and research barriers, and priorities. Results: Responses totaled 116 and came from Christian health and development organizations in Africa, Asia, and North America. The survey revealed three organizational research priorities and areas of desired assistance from a collaborative: 1) disseminating impacts, 2) evaluation skills and resources, including integral mission measurement tools, and 3) research design resources and services. Interests varied depending on whether the organization was based inside or outside of the United States. Discussion: The study aimed to identify priorities and barriers of Christian health organizations around research and outcomes evaluation. The findings suggest that a Christian research collaborative is not only feasible but could serve organizations throughout the world that have a desire to conduct more rigorous evaluation and research studies and disseminate and publish their results yet lack the time, knowledge, or resources to do so. Future studies should explore financial support systems to sustain a collaborative and create a model that could accommodate the different research and evaluation priorities depending on the location of the organization.